Techniques of zero base budgeting - Joshi, P L (Bombay, 1988)
The book would be of immense value to practising managers, administrators, Chartered and Cost Accountants in introducing and monitoring ZBB in their respective organisations. The book would be equally useful for the post-graduate students of Management, Commerce, Economics, Public Administration .
Keywords: Zero-base budgeting